Determinants of breastfeeding initiation in Ireland. (August 2016) - Gallagher, L.; Begley, C.; Clarke, M.
Abstract Background Ireland continues to rank among countries with the lowest breastfeeding initiation rates. National and regional studies also show that few women in Ireland who initiate exclusive breastfeeding continue to breastfeed for the recommended 6 months. Aim To assess the rate of exclusive and partial breastfeeding in Ireland at three time periods: birth to 48 h, 3–4 months following birth, and when the infant was 6–7 months old. Methods A longitudinal national cohort survey of 2527 mothers. Results Findings show that just 56 % (n = 1002) of mothers initiated breastfeeding at birth and, at 48 h, 42 % (n = 1064) of women were exclusively breastfeeding their babies. At 6–7 months, only 2.4 % of the 2527 mothers who took part, reported exclusive breastfeeding. Irish women were less likely to initiate breastfeeding (52.6 %) compared with Polish (82.2 %), British (64.5 %), and other nationalities (74.6 %). Multivariate analysis also revealed significant relationships between initiation and socio-economic variables, with mothers' health insurance status being of particular importance. Conclusion The results highlight the necessity to support the initiation and maintenance of breastfeeding in Ireland, in order to reduce rates of infant morbidity.